Validasi Modul Pembelajaran Fisika Berbasis Inkuiri pada Materi Pelajaran Hukum Newton tentang Gerak dan Gravitasi - Mona Trisna Cahyati; Hufri Hufri; Harman Amir (PILLAR OF PHYSICS EDUCATION, 2018)
Physics learning is done in accordance with the mandate of the 2013 curriculum that students actively find their own knowledge. The fact in School shows that inquiry learning in physics has not been applied well, and used  of teaching materials is still limited that support the process of learning implementation. Solution that can be done is to create an inquiry self-based physics learning module. The purpose of this study was to determine the validity of the physics-based inquiry learning module and RPP on Newton's legal material about motion and gravity.Research carried out including the type of Research and development (R & D). The object of this research is physics based inquiry and RPP. Based on the data analysis that has been done can be stated the results of the research that the validity of the product has a high level of validity with the average value of validation of physics-based inquiry learning module that is 89.47 and RPP is 90.74 with the criteria of each the same is very valid. It can be concluded that in the investigation of the validation of the physics-based physics learning module on newton's legal material about motion and gravity is very valid for use in physics learning of class X of SMA 2nd semester.